Therapy together: A caregiver led constraint induced movement therapy program for preschool aged children utilizing a virtual environment due to COVID 19. Issue 1 (2nd January 2023) - Shierk, Angela; Roberts, Heather; Dubberly, Katherine; Clegg, Nancy J.; Fagan, Marcus; Baldwin, Deborah; Reyes, Fabiola; VanPelt, Jonathan; Delgado, Mauricio R.
ABSTRACT: To pilot Therapy Together, an 8-week parent-led pediatric constraint induced movementtherapy ( P -CIMT) program for preschool aged children with unilateral cerebral palsy (UCP). Five children with UCP and their caregivers participated in eight, 1 hour group sessions structured by the TEAM approach (topic, encourage, activity, and motivate). Three of the sessions were in person and 5 of the sessions were online due to COVID 19. Parent coaching and therapeutic activities for each weekly session aimed to improve a specific upper limb domain. The caregivers were asked to implement therapeutic activities 1 hour each day at home. The primary outcome measure was the Assisting Hand Assessment (AHA), scored by a blinded rater. The secondary outcome measure was the Canadian Occupational Performance Measure (COPM). Caregivers kept a log of hours completed at home, comments about implementing the program, and rated their child's unilateral and bilateral hand performance weekly. Participants demonstrated clinically significant changes in bimanual performance (AHA) with a large effect size, but statistical significance was not reached. Improvements in occupational performance and satisfaction (COPM) were clinically and statistically significant. Therapy Together is a promising P -CIMT intervention program for preschooler with UCP. The program incorporates caregiver education and coaching with caregiver-led home therapeutic activities to improve children's bimanual hand skills and occupational performance while addressing barriers to intervention access such as caregiver hesitancy in order to reduce health disparities in children with UCP.